2008
DOI: 10.1017/s0001924000002190
|View full text |Cite
|
Sign up to set email alerts
|

Indirect aircraft structural monitoring using artificial neural networks

Abstract: From necessity, military aircraft often operate in a highly fatigue damaging environment and history has shown in lost lives and aircraft the consequences of failure to appreciate fully the usage environment. The need for robust and cost effective structural usage monitoring of military aircraft to ensure operations are conducted within acceptable levels of risk is paramount. Furthermore, increased economic pressures require ever-inventive methods to be employed to maximise the lives of military fleets; struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It is concluded that this technology could provide the basis for accurate, costeffective structural usage monitoring systems. Consequently in [18] and [19] a structural health and usage neural network (SHAUNN) monitoring system is proposed to predict stresses, strains, loads, or fatigue damage from flight parameters.…”
Section: Methods Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is concluded that this technology could provide the basis for accurate, costeffective structural usage monitoring systems. Consequently in [18] and [19] a structural health and usage neural network (SHAUNN) monitoring system is proposed to predict stresses, strains, loads, or fatigue damage from flight parameters.…”
Section: Methods Descriptionsmentioning
confidence: 99%
“…Other publications like [11,17,18] follow the same approach to model the loads at the vertical tail plane of an aircraft in dependency of aircraft system parameters and include additional input parameters such as the deflection of flaps and ailerons. Table 1 summarises the selected parameters used within this paper for each of the considered loads.To simplify, obtaining a mapping function describing the relation between the input and the output parameters basic physical laws are used [17] to combine the selected input parameters to reflect the relation present between the chosen input parameters and the considered output parameters.…”
Section: Parameter Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, health and usage monitoring of helicopters is an important research area (Wallace et al , 2004). Engineering health‐monitoring systems are often based on a mathematical model of the system, which is used to simulate the effect of damage on the system behavior (Reed, 2008; Trendafoilova et al , 2009; Ganguli et al , 1998). The development of a rotor helicopter health‐ and usage‐monitoring systems requires a mathematical model of the damaged rotor system.…”
Section: Helicopter Rotor Health Monitoringmentioning
confidence: 99%
“…Azzam et al [16] also described the development of methods to predict damage in helicopter components and the prediction of high-frequency events, such as buffet loading on the fin of a fixed-wing aircraft. The work reported in the current paper was inspired by the work of Reed [18,19], who developed an ANN-based parametric fatigue monitor for the wing and tailplane of a military trainer aircraft and the wing of a combat aircraft.…”
Section: Introductionmentioning
confidence: 99%